2018
DOI: 10.1039/c8dt02727g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of structure variations on the quadruplex DNA binding ability of nickel Schiff base complexes

Abstract: Two different series of nickel Schiff base complexes were prepared as part of a study aimed at discovering new compounds with high affinity and selectivity for quadruplex DNA (qDNA). The new complexes were prepared by modification of a literature method for synthesising N,N'-bis-(4-((1-(2-ethyl)piperidine)-oxy)salicylidene)phenylenediaminenickel(ii) (complex (1)). For Series 1 complexes, the phenylenediamine head group of the literature complex was replaced with ethylenediamine, phenanthrenediamine, R,R- and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 75 publications
2
7
0
Order By: Relevance
“…The C7-N1 bond lengths for both complexes were in the range of a double bond coordinate to the metallic ion concerning symmetrical Ni(II) complexes analogs. 28,68,69 The Ni-N and Ni-O bond lengths for both molecular structures agree with those reported for most symmetrical analogs. 28,68,69 The crystal packing of the Ni II -L 1 complex (Fig.…”
Section: X-ray Crystal Structures Of Ni II -L 1 and Ni Ii -L 2 Complexessupporting
confidence: 83%
“…The C7-N1 bond lengths for both complexes were in the range of a double bond coordinate to the metallic ion concerning symmetrical Ni(II) complexes analogs. 28,68,69 The Ni-N and Ni-O bond lengths for both molecular structures agree with those reported for most symmetrical analogs. 28,68,69 The crystal packing of the Ni II -L 1 complex (Fig.…”
Section: X-ray Crystal Structures Of Ni II -L 1 and Ni Ii -L 2 Complexessupporting
confidence: 83%
“…We and others have previously shown that square planar metal salphen complexes can be excellent G4 binders . While in some cases these complexes have shown good selectivity, this is still not high enough to bind to G4s specifically in the presence of a large excess of duplex DNA—as is the case in a cellular environment.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously shown that square planar metal salphen complexes can be excellent G4 binders. [14,[19][20][21][22][23][24][25][26] While in somec ases these complexes have shown good selectivity,t his is still not high enought ob ind to G4s specifically in the presence of al arge excess of duplex DNA-as is the case in ac ellular environment. This is partly due to the fact that planar compounds can potentially intercalate in-between base pairs of duplex DNA or even bind to its grooves.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this concept, other metals were used and various complexes were developed: Ni(II), Pd(II), Cu(II), Co(III), Pt(II), or Zn(II) [ 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 ]. Most of these salphen or salen complexes display a square planar geometry except the square-based pyramidal salphen complexes based on Co(III) [ 168 ].…”
Section: Classification and Characteristics Of G4 Ligandsmentioning
confidence: 99%